ENHANCING ENVIRONMENTAL VOCABULARY THROUGH ECOLINGUISTIC TEXTS: AN EXPERIMENTAL STUDY WITH UPMI ENGLISH LEARNERS - Puji Hariati (VISION, 2025)
This study examines the effectiveness of ecolinguistic texts in enhancing environmental vocabulary acquisition among English Education students at Universitas Pembinaan Masyarakat Indonesia (UPMI). Employing a quasi experimental pre-test post-test control group design, the study involved 60 second-year students divided equally into experimental and control groups. The experimental group received instruction through ecolinguistic texts integrating environmental themes, while the control group used conventional English materials. Data were analyzed using paired-sample and independent-sample t-tests. The findings reveal a statistically significant improvement in environmental vocabulary mastery in the experimental group compared to the control group. These results suggest that ecolinguistic texts provide meaningful contextualization, support semantic networking, and foster deeper lexical engagement. The study contributes to sustainability-oriented English language teaching and supports the integration of ecolinguistics into EFL curricula as part of Education for Sustainable Development (ESD).